Timing for animation - Whitaker, Harold; Halas, John. (London Focal Press, 2009)
A classic of animation education since it first published in 1981. Copies of Timing for Animation have been sitting dog-eared and spine-split on desks and workstations around the world, wherever animation is produced for more than 25 years. All you need to breathe life into your animation is at your fingertips. All the vital techniques employed by animators worldwide are explained using dozens of clear illustrations and simple, straightforward directions. Learn how animations should be arranged in relation to each other, how much space should be used and how long each drawing should be shown for maximum dramatic effect. Fully revised and updated, the second edition includes timing for digital production, digital storyboarding in 2d, digital storyboarding in 3d, the use of After Effects and much, much more! *Animate it right first time with these tried and tested techniquesby industry legends, Halas and Whitaker. The second edition is fullyupdated for digital workflows, by Tom Sito, animator of Beauty and the Beast and Shrek. * Get straight to the good stuff with simple, no-nonsense instruction on the key techniques like stretch and squash, animated cycles, overlapping, and anticipation. Learn how animations should be arranged in relation to each other, how much space should be used and how long each drawing should be shown for maximum dramatic effect. * Fully revised, in Full colorand updated, the second edition includes timing for digital production, digital storyboarding in 2d, digital storyboarding in 3d, the use of After Effects and much, much more!
Keywords: Animation (Cinematography).